P116. DBS electrode imaging using 3D transcranial ultrasound – A feasibility study with first quantitative results. Issue 8 (August 2015) - Ahmadi, S.-A.; Plate, A.; Schuberth, M.; Milletari, F.; Navab, N.; Bötzel, K.
<x xml:space="preserve">Abstract</x> Purpose Deep Brain Stimulation (DBS) is an established surgical treatment for neurodegenerative diseases such as Parkinson's Disease (PD) or Dystonia. In terms of imaging, pre-operative MRI scans are used for surgical planning and post-operative CT scans for control of electrode placement. Intra-operatively, however, imaging guidance is often avoided, due to contra-indications of DBS electrode contacts with MRI and difficulty of acquiring CT scans. Ultrasound imaging could be an attractive alternative, but has not been investigated yet due to difficult positioning of the transducer in the narrow burr-holes. Recently, there has been interest in the community towards the usage of non-invasive transcranial ultrasound (TCUS) through the pre-aureal bone window. In a seminal work (Walter, 2012 ), Walter described the intra-operative usage of TCUS for lead electrode imaging and post-operative placement assessment of DBS electrode, showing its potential and limitations. In this work, we investigate, for the first time, the feasibility of using 3D-TCUS for imaging of already implanted Deep Brain Stimulation (DBS) electrodes. As a first step towards this goal, we report electrode localization errors outside of the operating room on six previously operated DBS patients. Methods Post-operative CT scans are registered to already acquired pre-operative T1 and T2 MRI sequences to localize the actual electrode tip locations in MRI. We then acquire 3D-TCUS sweeps and co-register them to the pre-operative MRI as well, using a head-surface point-cloud registration first (using Iterative Closest Points, ICP) and a manual refinement using several pairs of corresponding points on anatomical structures (midbrain, ventricles) in TCUS and MRI. The comparison between electrode tips identified in 3D-TCUS and actual tip positions in CT are a first step towards assessing whether 3D-TCUS could provide a benefit intra-operatively in future. Results Quantitative evaluation is performed by reporting the accuracy of electrode tip localization after ICP-based registration (mean 5.62 mm, stdev 2.26 mm) and after manual registration refinement (mean 4.09 mm, stdev 1.75 mm). Additionally, we provide multiple image examples showing the dependence of 3D-TCUS quality depending on the bone window, and multiple examples of image artifacts in TCUS images and 3D reconstructions. Conclusions Intra-operative 3D ultrasound imaging has potential for electrode tip localization during DBS procedures. 3D transcranial US could be an attractive alternative to intra-cranial imaging through the narrow burr-hole. We report the first results of volumetric 3D-TCUS imaging on already operated patients in a post-operative scenario. Initial results still show a relatively high inaccuracy of electrode tip localization, e.g. due to TCUS artifacts and imperfect registration to the pre-operative MRI. Nevertheless, the potential of TCUS for DBS electrode imaging as described by Walter (2012) can be extended to 3D, allowing for electrode tip and shaft localization. This motivates further work, e.g. on improved MRI-US registration and computer-aided tip detection (Figs. 1 and 2).